GERAKAN LITERASI PADA PEMBELAJARAN BAHASA INDONESIA SMP DI PALANGKA RAYA (FKIP, Universitas Palangka Raya, 2020)
This research specifically is (1) to determine the role of literacy in learning Indonesian at SMP in Palangka Raya, (2) to determine the function of literacy in learning Indonesian at SMP in Palangka Raya, (3) to determine the application of literacy movements in learning Indonesian at SMP in Palangka Raya. This type of research uses a qualitative descriptive approach. The object of research is the distribution of questionnaires (questionnaires) filled with 120 students at SMP Palangka Raya and Indonesian language teachers at SMP Palangka Raya. The questionnaire was analyzed, the focus of the analysis was the application of the school literacy movement. Based on the results of the study it can be concluded that (1) The role of the literacy movement in learning Indonesian at SMP in Palangka Raya can be categorized as very good with the highest percentage of students, namely 83% and the percentage of teachers 85% with very good percentage, (2) The function of literacy movements in learning Indonesian SMP in Palangka Raya can be categorized as good with the highest percentage of students, namely 78% and the percentage of teachers 100% in the very good category, (3) The application of the literacy movement in learning Indonesian at SMP in Palangka Raya can be categorized as good the highest in students is 87% and the percentage of teachers is 100% in the very good category.